2010
DOI: 10.1139/z10-056
|View full text |Cite
|
Sign up to set email alerts
|

Den-site selection is critical for Pallas’s cats (Otocolobus manul)

Abstract: We evaluated the habitat selection of 101 den sites used by 21 individual Pallas’s cats ( Otocolobus manul (Pallas, 1776) = Felis manul Pallas, 1776) in summer, winter, and the maternal period in central Mongolia using generalized linear mixed models. Pallas’s cats used rock crevices and marmot burrows as dens for giving birth, raising young, thermoregulation, feeding, mating, and as important cover from predators. Den sites were selected with higher proportions of rocky and ravine habitats in the surroundings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 24 publications
0
31
1
1
Order By: Relevance
“…Previous studies exploring the responses of eastern bettongs to fragmentation and habitat characteristics highlighted the importance of habitat amount and quality in determining their occurrence (Gardiner et al, 2018) Previous studies of habitat preferences in eastern bettongs suggested a lack of preference for particular floristics and vegetation structure (Johnson, 1994a); however, our study highlights behavioral responses to the understorey density of vegetation at ground level and to tree-canopy cover. Finding appropriate shelter is important for the survival of species, as this can include concealment from predators, rearing young and resting during inactive periods as seen across species such as hyenas (Singh, Gopalaswamy, & Karanth, 2010), lobsters (Heldt, 2013), and Pallas' cats (Ross, Kamnitzer, Munkhtsog, & Harris, 2010). Bettongs den in nests that they construct from material such as grass, fibrous bark, and bracken ferns.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies exploring the responses of eastern bettongs to fragmentation and habitat characteristics highlighted the importance of habitat amount and quality in determining their occurrence (Gardiner et al, 2018) Previous studies of habitat preferences in eastern bettongs suggested a lack of preference for particular floristics and vegetation structure (Johnson, 1994a); however, our study highlights behavioral responses to the understorey density of vegetation at ground level and to tree-canopy cover. Finding appropriate shelter is important for the survival of species, as this can include concealment from predators, rearing young and resting during inactive periods as seen across species such as hyenas (Singh, Gopalaswamy, & Karanth, 2010), lobsters (Heldt, 2013), and Pallas' cats (Ross, Kamnitzer, Munkhtsog, & Harris, 2010). Bettongs den in nests that they construct from material such as grass, fibrous bark, and bracken ferns.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson, 1998;Li et al, 2015), refuges (Emsens et al, 2013), daytime shelters (Kowalczyk, Zalewski & Jêdrzejewska, 2004;Mysłajek, Nowak & Je z drzejewska, 2012) and daytime rest burrows (Endries & Adler, 2005). Rest sites are places of rest and not linked to reproduction unlike den sites (see Ruggiero, Pearson & Henry, 1998;Ye et al, 2007;Ross et al, 2010;P eriquet et al, 2016 for den site characteristics). Rest sites are also key locations for many animals as they influence the risks of predation and/or parasitism (Emsens et al, 2013;Li et al, 2015), maintain social bonds or territories (Anderson, 1998;Endries & Adler, 2005) and maximize access to food or water resources (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…But in some, rare cases, breeders build multiple nests from which to choose for reproduction (e.g., marsh wren: Verner & Engelsen, 1970;European wren: Garson, 1980; Australian reed warblers: Berg, Beintema, Welbergen, & Komdeur, 2006;raptors: Ontiveros, Caro, & Pleguezuelos, 2008;Pallas's cats: Ross, Kamnitzer, Munkhtsog, & Harris, 2010). Whether nests are used once and abandoned, used repeatedly within and across breeding seasons (i.e., high nest site fidelity), and/or are used singly or by multiple nesting individuals is equally variable (e.g., Ross et al, 2010;Lovich et al, 2014;Robert et al, 2014).…”
Section: ;mentioning
confidence: 99%
“…In most vertebrates, one or both parents invest in a single nest per breeding attempt, such that unless the nest is disturbed (e.g., Beckmann, Biro, & Martin, ; Flegeltaub, Biro, & Beckmann, ), whether it is used goes more or less without question. But in some, rare cases, breeders build multiple nests from which to choose for reproduction (e.g., marsh wren: Verner & Engelsen, ; European wren: Garson, ; Australian reed warblers: Berg, Beintema, Welbergen, & Komdeur, ; raptors: Ontiveros, Caro, & Pleguezuelos, ; Pallas's cats: Ross, Kamnitzer, Munkhtsog, & Harris, ). Whether nests are used once and abandoned, used repeatedly within and across breeding seasons (i.e., high nest site fidelity), and/or are used singly or by multiple nesting individuals is equally variable (e.g., Ross et al, ; Lovich et al, ; Robert et al, ).…”
Section: Introductionmentioning
confidence: 99%